Manajemen Strategi Kepala Sekolah dalam Membangun Budaya Organisasi di SMP IT Luqmanul Hakim Aceh Besar - Muhammad Ilham; Aulia Rahmat (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
The goal of this study is to describe and comprehend the principal of SMP IT, Luqmanul Hakim, in terms of organizational culture development and implementation. The methodology employed is a qualitative one with a descriptive focus. Three individuals at SMP IT Luqmanul Hakim served as data sources for this study: the principal, the head of administration, and a teacher in the field of study. Observation, interviewing, and documenting procedures are used to collect data. The data analysis process included data reduction, data display, and conclusion drafting. The findings of this study indicate that the principal's strategy for fostering organizational culture is to make work commitments, establish regular management, assign primary work to each teacher and employee, frequently direct teachers and employees, choose teachers with good character and who adhere to school regulations, direct teachers and students in fostering morals, etiquette, and manners, acclimating students to dhuha prayer, and including dhuha prayer in the curriculum. The principal's strategy for implementing organizational culture is to communicate the primary objectives and responsibilities to each teacher, as well as to conduct weekly training and recitations, as well as to supervise and control each teacher and student to ensure that they are aware of the school environment's conditions.